The effects of laser diode treatment on liver dysfunction of Mus musculus due to carbofuran exposure: An in vivo study - Astuti, Suryani Dyah; Victory, Vivi Sumanti; Mahmud, Amalia Fitriana; Putra, Alfian Pramudita; Winarni, Dwi (Journal of Advanced Veterinary and Animal Research, 2019)
Objective: The aim of this study is to determine the effect of laser diode as an alternative treatment on liver dysfunction (in vivo study) that is caused by carbofuran using male mice (Mus musculus) strain Balb/C. Materials and Methods: The samples were divided into three groups, namely, Group C–L– (control group, no treatment), Group C+L– (only treated by carbofuran treatment), and Group C+L+ (treatment group, treated by carbofuran and laser-puncture) with five replications each. After being treated, each liver slice of samples was observed using microscope to get the histology result and then scored. Results: Carbofuran contamination can lead to inflammation of cells and necrosis. The histology results and the scoring test showed that the liver cells repair with the energy dose of laser diode at 0.5 and 1.0 Joule. Conclusion: The optimum energy dose in this study was 1.0 Joule which had the closest score of inflammatory cells and necrosis to normal liver cells. J. Adv. Vet. Anim. Res., 6(4): 499-505, December 2019